Development of gametophytes of Thelypteris patens (Swartz) Small and Thelypteris puberula (Baker) Morton var. puberula - Reyes Jaramillo, Irma; Perez-Garcia, Blanca (Instituto de Ecología, A.C., 1995)
The development of the gametophytes of Thelypteris patens (Swartz) Small and Thelypteris puberula (Baker) Morton var. puberula is described in this paper. In both species the laminar, bidimensional stage follows a brief filamentous stage, which has a few cells. The adult prothalia are reniform or cordiform, with both marginal and superficial hairs. Gametangia are present 2-3 months after the sowing of the spores, and they are of the common type in advanced ferns. This significant differences between these species are size and abundance of hairs, shape of the adult prothalia, type of rhizoids, and the early development of the young sporophyte in Thelypteris patens.